Social Harmonization Values and Local Wisdom in the Cathering Culture of Wedding Ceremonies in Madura - Khotijah, Sitti; Hidayati, Nurul; Annisa, Anni (IAIN Madura, 2023)
The sense of tolerance and community is highly upheld to create social harmony. However, as time went on, the community values were increasingly eroded due to the entry of a new culture, namely the catering culture which slowly shifted local traditions in the ceremonial marriage of the Madurese community, especially in kitchen matters which were originally cohesiveness, togetherness, intimacy, harmony, and high friendship become an individualist, hedonist society who prefers something instant and easy to put aside the values of harmonization among others. So, this study is intended to study further and more deeply about the values of social harmonization and local wisdom in the culture of catering wedding ceremonies in Madura. This research is qualitative approach with a descriptive study. The object of this research was Soloh Dajah Hamlet, Murtajih Village, Pademawu District, Pamekasan Regency. The results of the study state that: First, there are several values of the wedding ceremony as a locus of a social harmonization and local wisdom, namely: Religious values, kinship values, cohesiveness and cooperation values, and tolerance and solidarity values. Second, at Madurese wedding ceremonies, people tend to use catering services to make it easy. Third, the inequality that occurs in the values of social harmonization and local wisdom in the catering culture of Madurese wedding ceremonies, namely: The formation of apathy and bad views of society.